Co-payment fee and utilisation of healthcare services: the case of out-patient insured patients at Aga-Khan Hospital Mombasa - Twahir, H. (Strathmore University, 2023)
Third party payers of health such as health insurance companies whom for a long time have been reporting losses (despite an increase in the premium contributions), introduced gate keeping measures such as co-payments to try to control utilisation of health services by patients by reducing hospital visits, consultation, laboratory and pharmaceutical costs. Co-payments introduce out of pocket payments health, a key component in reducing universal health care. The effectiveness of these co-payments in reducing utilisation of health services/ health costs and resulting in savings for the health insurance companies is however still unclear, with some studies arguing that it has little or no effect and some actually having opposite effects of increasing health costs. This was a retrospective cross-sectional study carried out at the Aga-Khan Hospital, Mombasa Outpatient department (OPD) centers amongst different patients seeking healthcare services at the facility. Study patients included all insurance patients seeking health services at these different OPD centres. Those on co-payments were compared with those on no co-payments, seeking to determine if the presence of co-payments affected utilisation of various healthcare services and if so by what extent and at what difference in costs. Utilisation of health was determined through assessing patient numbers and cost. Data of more than 108,000 patients who visited the hospital over a 12-month period in the year 2021 was obtained from the Hospital Management Information System. Descriptive analysis was done presenting counts (percentages) and means (standard deviations) of the different variables. Bivariate analysis tests for differences in the hospital visits among the co-pay groups was done using Chi square tests for categorical variables and one-way analysis of variance (ANOVA) and median tests for the continuous variables, presenting the p values. Utilisation of health services was analysed by mainly comparing number of visits and costs of the different health services in the study population. The co-payment group was further divided into four tiers of co-payments (Kshs 1-500, 501-1000, 1001-1500 and 1501-2000). The findings showed that co-payments generally had the effect of increasing cost of utilisation of healthcare compared to when there was no co-payment and also affected the number of patients attempting to utilise health. Co-payment tier of Kshs 1-500 had the highest number of patients seen for those on co-payment and the number of patients generally decreased as co-payment increased. In conclusion, the study showed that, co-payments affected the overall costs of a patient visit to the hospital. There was also a significant difference in the consultation costs, laboratory costs and pharmaceutical costs per hospital visit of those on co-payment comparing those not on co-payment with those on co-payment paying more to see a doctor at the outpatient department compared to those not on co-payment. The overall utilisation costs per visit were also significantly higher in those who paid co-payment versus those that did not. Analysis of the different tiers of co-payments showed a significant difference in cost of utilisation in some aspects of healthcare in some tiers of co-payments. These results can thus be used by both the insurance companies and other stakeholders in the health industry to influence policy on health financing.
Full - text thesis